Examining equity of walking accessibility to green spaces: A case study of Islamabad - Muhammad Muzzamil Hussain Khattak; Muhammad Asif Khan; Sameer Ud Din; Muhammad Zaheer Khan; Muhammad Faisal Habib (Ain Shams Engineering Journal, 2023)
Parks, playgrounds, and other green spaces, in a region, help in promoting the active lifestyle of its residents. Pakistan has an emerging problem of obesity due to the inactive lifestyle of people, especially in urban areas. Obesity is considered a root cause of diseases like cardiovascular disease, type 2 diabetes, hypertension, and other life-threatening health conditions. The intensity of this problem can be reduced by providing amenities to the citizens to promote physical activities like walking and sports. Walking facilities and their impacts on the health and environment are usually ignored in Pakistan’s urban development and policymaking for public transportation. This results in an inequitable transportation system within an urban area considering the notions of vertical equity. This study examines the walking accessibility to green spaces from residential sectors of Islamabad city using spatial interaction/gravity model using impedance OD matrix based on the road network of the said region. The study area was divided into grids and spatial equity analysis was performed using the Lorenz curve and the Gini coefficient was used as a performance measure to describe the overall inequality across the community. This research will help urban planners and policymakers to prioritize the interventions to enhance societal equity by improving walking accessibility to green spaces across the region.